Hypertension in India: a gender-based study of prevalence and associated risk factors - Raza Mohammad; Dhananjay W. Bansod (BMC, 2024)
Abstract Background Hypertension, a major non-communicable disease, is responsible for a significant number of global deaths, including approximately 17.9 million yearly. The Global Burden of Disease 2019 (GBD 2019) estimates that 19% of global deaths are attributed to elevated blood pressure. India, with a population of over 1.4 billion, is facing a serious challenge in combating this silent killer. This study aims to analyze the gender-based prevalence of hypertension in India and explore its associated risk factors using data from the fifth National Family Health Survey (NFHS-5). Methods NFHS-5 collected data from 636,699 households across all states and union territories. The study includes standardized blood pressure measurements for 17,08,241 individuals aged 15 and above. The data were analyzed using Stata, employing descriptive statistics for the assessment of the prevalence and binary logistic regression to identify predictors of hypertension. Results The study found the overall prevalence of hypertension in India to be 22.6%, with men (24.1%) having a higher prevalence than women (21.2%). Prevalence increased with age, reaching 48.4% in individuals aged 60 and above. Urban residents had a slightly higher prevalence (25%) than rural residents (21.4%), indicating the rapid spread of hypertension across all populations. Regional variations were observed, with the highest prevalence in Sikkim (37.9%) and the lowest in Rajasthan (16.5%). Increasing age, urban residence, belonging to certain religions (Muslim and other than Hindu or Muslim), and being classified as Scheduled Tribes (ST) were associated with a higher likelihood of hypertension. Conversely, belonging to Scheduled Castes (SC) or Other Backward Classes (OBC), being currently unmarried, and having higher education were associated with a lower likelihood of hypertension. Wealth index analysis revealed that those in the richest quintile were more likely to have hypertension. Behavioural risk factors, such as alcohol consumption, overweight, obesity, increased waist circumference, and high blood glucose levels, are positively associated with hypertension. Conclusion Hypertension is a significant health burden in India, affecting both men and women. Age is the strongest non-modifiable predictor for both men and women. However, ageing women have higher odds of hypertension than ageing men, and this distinction becomes much more evident in their older ages. Obese women, based on BMI, have higher odds of hypertension than men. However, hypertension prevalence is slightly higher among men who are overweight or obese compared to women. BMI, waist circumference, random glucose level, alcohol use, and education level emerged as major predictors. Health education and awareness campaigns are critical to control the growing burden of hypertension in India. Policymakers must focus on preventive measures, targeting lifestyle changes and improved healthcare access for both men and women. By addressing these risk factors, India can make significant progress in controlling hypertension and reducing its impact on public health.